2017
DOI: 10.1016/j.cyto.2017.01.004
|View full text |Cite
|
Sign up to set email alerts
|

High dilutions of antimony modulate cytokines production and macrophage – Leishmania (L.) amazonensis interaction in vitro

Abstract: Both dilutions were able to potentiate the decrease of most of cytokines and chemokines induced by the parasite infection in vitro, which explains the clinical improvement seen previously in vivo, however, the mechanisms involved and the epidemiological significance of these findings are still under discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 62 publications
3
25
0
Order By: Relevance
“…29 It was later identified that the clinical improvement was due to the reduction in certain cytokines, which had increased in response to the infection, and the blocking of chemokine CCL2 (MCP-1), known for monocyte recruitment and parasite multiplication. 30 Similarly, in the present investigation, the decrease in infection may be due to an improvement in the suppressed immune system caused by VL. Similar results were reported by Cajueiro et al, 31 in which BioLi 30x treatments significantly induced morphological alterations and increased nitric oxide production in the in-vitro assay of L. infantum promastigotes.…”
Section: Parasite Loadsupporting
confidence: 70%
“…29 It was later identified that the clinical improvement was due to the reduction in certain cytokines, which had increased in response to the infection, and the blocking of chemokine CCL2 (MCP-1), known for monocyte recruitment and parasite multiplication. 30 Similarly, in the present investigation, the decrease in infection may be due to an improvement in the suppressed immune system caused by VL. Similar results were reported by Cajueiro et al, 31 in which BioLi 30x treatments significantly induced morphological alterations and increased nitric oxide production in the in-vitro assay of L. infantum promastigotes.…”
Section: Parasite Loadsupporting
confidence: 70%
“…12 The in-vitro effect of homeopathy on living cells is scientifically consolidated by several renowned studies and without requiring animal models. 13 These effects have already been reported for bacteria, 12,14 protozoa, 15,16 fungi, 17 cell cultures, 18,19 and reproductive cells of mammals. 20 Recently, effects of homeopathic medicines have been demonstrated on the bacterium Streptococcus pyogenes.…”
Section: Introductionmentioning
confidence: 78%
“…14 There is also a recent report of intense immunomodulatory effects upon exposure to homeopathic medicines on inflammatory mechanisms of cell cultures infected by the protozoon Leishmania amazonensis due to exposure to homeopathic medicines. 16 Nevertheless, the effect of homeopathy on dipterous larvae has not been scientifically reported to date.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism by which ultra-high dilutions interact with solvatochromic dyes is still being elucidated, though evidence so far indicates that such dilutions are polarizing, inducing dipole moment changes. 18 Recently, correspondence between the effects of the homeopathic medicine Antimonium crudum on solvatochromic dyes and the effects of the same dilutions in an in vitro model using macrophages infected with Leishmania amazonensis 22 has been demonstrated. 20 This has opened up new avenues of study in the field of high dilution research and possible mechanisms of action, in which the effects of ultra-high dilutions on solvatochromic dyes could be considered as a physico-chemical indicator of their biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study developed in our laboratory on the physicochemical properties of the drug Antimonium crudum 19,20 has shown that absorbance variations of solvatochromic dyes presented a clear relation with the biological effects of this drug in vitro and in vivo. 21,22 These findings suggest that solvatochromic dyes could be used as physico-chemical probes of biologically active high dilutions of different substances beyond Avogadro's number, based on dipole moment changes. 23 Discovering if solvatochromic dyes are sensitive enough to detect changes in the polarity of large water volumes would be a critical step in evaluating the plausibility of using high dilutions in many field situations, such as environmental management, 24 organic agriculture 25 and in herd, broiler, and fish breeding, with a view to improving productivity.…”
Section: Introductionmentioning
confidence: 95%